Novel mitochondrial tRNAIle m.4282A>G gene mutation leads to chronic progressive external ophthalmoplegia plus phenotype. Issue 10 (17th July 2014) - Jackson, Christopher B; Neuwirth, Christoph; Hahn, Dagmar; Nuoffer, J-M; Frank, Stephan; Gallati, Sabina; Schaller, André
Abstract : Background/aim: To investigate the underlying pathomechanism in a 33-year-old female Caucasian patient presenting with chronic progressive external ophthalmoplegia (CPEO) plus symptoms. Methods: Histochemical anaylsis of skeletal muscle and biochemical measurements of individual oxidative phosphorylation (OXPHOS) complexes. Genetic analysis of mitochondrial DNA in various tissues with subsequent investigation of single muscle fibres for correlation of mutational load. Results: The patient's skeletal muscle showed 20% of cytochrome c oxidase -negative fibres and 8% ragged-red fibres. Genetic analysis of the mitochondrial DNA revealed a novel point mutation in the mitochondrial tRNA Ile ( MTTI ) gene at position m.4282G>A. The heteroplasmy was determined in blood, buccal cells and muscle by restriction fragment length polymorphism (RFLP) combined with a last fluorescent cycle. The total mutational load was 38% in skeletal muscle, but was not detectable in blood or buccal cells of the patient. The phenotype segregated with the mutational load as determined by analysis of single cytochrome c oxidase -negative/positive fibres by laser capture microdissection and subsequent LFC-RFLP. Conclusions: We describe a novel MTTI transition mutation at nucleotide position m.4282G>A associated with a CPEO plus phenotype. The novel variant at position m.4282G>A disrupts the middle bond of the D-stem of the tRNA Ile and is highly conserved. The conservation and phenotype-genotype segregation strongly suggest pathogenicity and is in good agreement with the MTTI gene being frequently associated with CPEO. This novel variant broadens the spectrum of MTTI mutations causing CPEO.